Extensive variation in gene copy number at the killer immunoglobulin-like receptor locus in humans. - Sanne Vendelbosch; Martin de Boer; Remko A T W Gouw; Cynthia K Y Ho; Judy Geissler; Wendy T N Swelsen; Michael J Moorhouse; Neubury M Lardy; Dirk Roos; Timo K van den Berg; Taco W Kuijpers (PLoS ONE, 2013)
Killer immunoglobulin-like receptors (KIRs) are involved in the regulation of natural killer cell cytotoxicity. Within the human genome seventeen KIR genes are present, which all contain a large number of allelic variants. The high level of homology among KIR genes has hampered KIR genotyping in larger cohorts, and determination of gene copy number variation (CNV) has been difficult. We have designed a multiplex ligation-dependent probe amplification (MLPA) technique for genotyping and CNV determination in one single assay and validated the results by next-generation sequencing and with a KIR gene-specific short tandem repeat assay. In this way, we demonstrate in a cohort of 120 individuals a high level of CNV for all KIR genes except for the framework genes KIR3DL3 and KIR3DL2. Application of our MLPA assay in segregation analyses of families from the Centre d'Etude du Polymorphisme Humaine, previously KIR-genotyped by classical techniques, confirmed an earlier reported duplication and resulted in the identification of a novel duplication event in one of these families. In summary, our KIR MLPA assay allows rapid and accurate KIR genotyping and CNV detection, thus rendering improved transplantation programs and oncology treatment feasible, and enables more detailed studies on the role of KIRs in human (auto)immunity and infectious disease.